Relationship between Plaque pH and Different Caries-Associated Variables in a Group of Adolescents with Varying Caries Prevalence - Aranibar Quiroz, E.M.; Alstad, T.; Campus, G.; Birkhed, D.; Lingström, P. (Caries research, 2014)
The pH response of the dental biofilm after a sugar challenge can be considered to mirror the acidogenic potential and thereby the caries risk of an individual. The aim of this cross-sectional study was to evaluate the relationship between plaque pH and different caries variables in adolescents with varying caries prevalence. One hundred individuals, aged 14-15 years, were examined regarding different caries-related variables: (i) caries score (DS m , DS i , DS m + i , DT m ), (ii) salivary secretion rate and buffer capacity, (iii) oral microflora of plaque and saliva, (iv) plaque amount, (v) plaque pH and (vi) dietary intake, oral hygiene habits and fluoride use. Plaque pH was assessed using the microtouch method before and after a 1-min mouthrinse with 10 ml 10% sucrose. Depending on the minimum pH, the participants were divided into three groups: low pH (≤5.3), medium pH (>5.3-6.3) and high pH (>6.3). Statistically significant differences between the three groups (p < 0.01) were found for initial caries (DS i ) and combined manifest and initial caries (DS m + i ). A statistically significant difference was also found in the log values for salivary lactobacilli (p = 0.02) within the three groups, and for the total number of bacteria in plaque (p = 0.04); for both variables, the low-pH group had the highest values. The only covariate significantly associated was the Cariogram score in the medium-pH group (p < 0.01) and the number of meals per day in the high-pH group (p = 0.02). To conclude, plaque pH measured by the microtouch method is a method that can be used for discriminating between individuals with varying caries prevalence.